Evaluation of Hormone Receptors Status in Breast Carcinoma (Journal of Shaheed Suhrawardy Medical College, 2019)
Background & objective: The importance of establishing hormone receptor status of tumors for the treatment of women with hormone receptor-positive breast cancer is often emphasized. It is critical to evaluate hormone receptor status when considering response to endocrine therapy. The present study was intended to evaluate the usefulness of hormone receptor status in breast carcinoma.Materials & Methods: The present study was conducted in the Department of Pathology, Dhaka Medical College, Dhaka over a period 12 months from July 2009 to June 2010. A total of 30 histopathologically diagnosed cases of breast tumors who were also subjected to immunohistochemical (IHC) test for ER, PR status and HER-2/neu were consecutively included in the study. Patients who have already been treated for malignancy or who had a history of receiving radiotherapy were excluded.Result: Age distributions shows that 40% of the patients were early middle-aged (30-40 years), 30% middle-aged and the rest were either < 30 years or >50 years old. Left breast was involved more often (56.7%) than the right breast (43.3%). The predominant location was upper outer quadrant (43.3%), followed by upper inner quadrant (20%), lower outer quadrant (20%), lower inner quadrant (10%) and central (6.7%). Over half (53.3%) of the tumors were < 5 cm and the rest 5 cm or more. Nearly half (46.7%) of the tumors were moderately differentiated, 36.6% well-differentiated and 16.7% poorly differentiated. In majority (83.3%) of the cases lymph-nodes (axillary lymph nodes) were involved. Based on estrogen and progesterone receptor status, over half (53.3%) of the tumors were ER and PR positive and 40% were Her2/neu overexpressed.Conclusion: The study concluded that half of the Bangladeshi breast cancer patients are ER and PR positive and two in every five cases are Her2/neu overexpressed.J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 70-73